1999
DOI: 10.3319/tao.1999.10.1.239(images)
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Oxygen Isotope Straigraphy for the Last 150,000 Years in the Southern South China Sea:Core MD972151

Abstract: A detailed high-resolution oxygen isotope stratigraphy over the last two glacial-interglacial cycles in the southern South China Sea is presented, based upon analysis of Globigerinoides sacculifer (planktic foraminifera) in Core MD972151. Major characteristic isotopic events were identified and correlated to the standard SPECMAP chronology. In addition, radiocar bon dating and a few biostratigraphic, geomagnetic and tephrochronologic markers were employed to enhance the reliability and resolution of the age mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…2b) reveals that glacial/interglacial variations of 1.5‰, in agreement with previous results (Thunell et al 1992;Schonfeld and Kudrass 1993;Lee et al 1999;Chen et al 2005;Zhao et al 2006). The mean values (~-2.11‰) for MIS 5 and Holocene (0 -4 ka) are also consistent with previously reported data.…”
Section: Oxygen Isotope Stratigraphy and Sedimentation Ratesupporting
confidence: 92%
“…2b) reveals that glacial/interglacial variations of 1.5‰, in agreement with previous results (Thunell et al 1992;Schonfeld and Kudrass 1993;Lee et al 1999;Chen et al 2005;Zhao et al 2006). The mean values (~-2.11‰) for MIS 5 and Holocene (0 -4 ka) are also consistent with previously reported data.…”
Section: Oxygen Isotope Stratigraphy and Sedimentation Ratesupporting
confidence: 92%
“…The last appearance datum (LA) of pink Globigerinoides ruber at about 120 ka has been considered a good biostratigraphic marker in the western Paci¢c (Thompson et al, 1979). Lee et al (1999) reported recently that the age of this datum is 127 ka at Site MD972151 in the southwest SCS. The last occurrence of pink G. ruber at Site MD972142 was found at a subdepth of 910 cm.…”
Section: Methodsmentioning
confidence: 99%
“…The age of the bottom of the acme zone in the Pacific has been dated to be at 85 ka (Berggren et al 1995). The absence of pink Globigerinoides ruber, on the other hand, delimits the sequence to be younger than 127 ka (Lee et al 1999;Wei et al 2000). Moreover, the persistent appearance of orange-colored tiny Zeaglobigerina rubescens indicates that the sediments recovered are young and fresh (Parker and Berger 1971).…”
Section: Biostratigarphic Constrains Of Hole 1202dmentioning
confidence: 99%